2012
DOI: 10.1016/j.peptides.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y activates phosphorylation of ERK and STAT3 in stromal vascular cells from brown adipose tissue, but fails to affect thermogenic function of brown adipocytes

Abstract: The thermogenic function of brown adipose tissue (BAT) is increased by norepinephrine (NE) released from sympathetic nerve endings, but the roles of NPY released along with NE are poorly elucidated. Here, we examined effect of NPY on basal and NE-enhanced thermogenesis in isolated brown adipocytes that express Y1 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…STAT3 phosphorylation at Ser727 residue has been shown to increase the transcriptional potential of STAT3, and the cooperation of both tyrosine (705) as well as serine (727) phosphorylation is necessary for full activation of Stat3 [ 41 , 42 ]. Shimada et al [ 21 ] has showed that NPY increased phosphorylation STAT3 at Ser 727 residue in stromal vascular cells from brown adipose tissue. Transcriptional activation of eukaryotic genes often requires the cooperative action of many proteins [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STAT3 phosphorylation at Ser727 residue has been shown to increase the transcriptional potential of STAT3, and the cooperation of both tyrosine (705) as well as serine (727) phosphorylation is necessary for full activation of Stat3 [ 41 , 42 ]. Shimada et al [ 21 ] has showed that NPY increased phosphorylation STAT3 at Ser 727 residue in stromal vascular cells from brown adipose tissue. Transcriptional activation of eukaryotic genes often requires the cooperative action of many proteins [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its molecular mechanism has not been fully elucidated. In stromal vascular cells and brain, NPY has been proved to modulate phosphorylation of STAT3 and expression of c-fos [ 20 , 21 ], which are important signaling molecules also involved in VSMC functions [ 22 ]. Since studies have revealed that plasma concentration of NPY is increased during hypertension in pregnancy and NPY is involved in the regulation of VSMC functions, we therefore hypothesized that NPY plays important roles in vascular remodeling during hypertension in pregnancy, which may involve STAT3 and c-fos pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen concentration in the chamber was monitored continuously for 5 min before and 10 min after the addition of 1 µM NE. NE concentration necessary to obtain the maximal effect in brown adipocytes was determined as described previously [32]. Oxygen consumption rates were calculated using computer software (782 System; Strathkelvin Instruments, Glasgow, Scotland).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, given that ERK phosphorylation is reported to be induced by NPY 35 38 especially during chemotaxis 39 , 40 and that the intracellular signalling cascade of NPY 12 converging on ERK is also able to amplify growth-promoting effects 34 , we asked if ERK phosphorylation was altered after blocking of NPY. Our data have shown that the blocking of NPY receptors did not alter ERK phosphorylation in ASCs respect to 10% PL (Fig.…”
Section: Resultsmentioning
confidence: 99%